2021
DOI: 10.1093/pm/pnab278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Low-Carbohydrate Ketogenic Diet on Reported Pain, Blood Biomarkers and Quality of Life in Patients with Chronic Pain: A Pilot Randomized Clinical Trial

Abstract: Background A low-carbohydrate ketogenic diet has been reported to improve chronic pain by reducing inflammation, oxidative stress, and sensitivity within the nervous system. The main aim of this trial is to evaluate the effects of a ketogenic diet on reported pain, blood biomarkers and quality of life in patients with chronic pain. Methods Participants with chronic musculoskeletal pain were recruited for a 12-week diet interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 50 publications
0
22
1
Order By: Relevance
“…Both demonstrated improvements in pain outcomes, one using a KD (78) and the other an LCD (77) ; however, neither presented ketone levels or measured dietary carbohydrate data. A third study (14) published after the scoping review date also reported significant improvements in pain outcomes using a KD protocol with a significant but small rise in ketone levels and measured daily carbohydrate intake reduced to 70 g per day in the intervention group. The human trials presented support the use of a KD for a reduction in nervous system sensitivity; however, an LCD also reports benefits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Both demonstrated improvements in pain outcomes, one using a KD (78) and the other an LCD (77) ; however, neither presented ketone levels or measured dietary carbohydrate data. A third study (14) published after the scoping review date also reported significant improvements in pain outcomes using a KD protocol with a significant but small rise in ketone levels and measured daily carbohydrate intake reduced to 70 g per day in the intervention group. The human trials presented support the use of a KD for a reduction in nervous system sensitivity; however, an LCD also reports benefits.…”
Section: Discussionmentioning
confidence: 97%
“…These included: (a) metabolic, energetic and biochemical changes, (b) restoration of cortical excitability to homoeostatic levels, (c) gene regulation, (d) improved mitochondrial function and number, (e) reduced neuroinflammation, (f) adaptive neuroplasticity, (g) neurotransmitter and synaptic regulation, (h) reduced oxidative stress and (i) activation of signalling pathways. We have also more recently identified a significant and clinically meaningful reduction in reported pain of patients undergoing a whole-food ketogenic diet intervention in a pilot clinical trial (14) .…”
Section: Introductionmentioning
confidence: 93%
“…In women with gestational diabetes, or overweight or obese adults, low-carbohydrate mixed meals had significantly reduced iAUC in blood glucose and/or insulin [ 27 , 28 ]. In addition, the intake of a low-carbohydrate ketogenic diet for 12 weeks had an effect in reducing body weight and BMI [ 29 ]. Gene expression involved in nutrient metabolism is also different during day and night and depends on meal composition [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although these two dietary interventions are gaining in popularity, there may not always be significant additional benefits to be gained from fasting [44] or LCD. For many people improving diets by reducing ultra-processed foods (increasing consumption of high-quality protein, and fresh fruits and vegetables) can improve inflammation and pain independent of carbohydrate levels [1,57]. For example, a positive correlation was found between the risk of metabolic syndrome and higher consumption of carbohydrates, particularly ultra-processed foods in Asian and less developed nations versus non-Asian, and more developed countries [7].…”
Section: Discussionmentioning
confidence: 99%